Influence of Different Rates of Phosphorus and Zinc Application to Micronutrients Uptake and DTPA Extractable Fe, Mn, Zn and Cu Status after Wheat (Triticum aestivum L.) Harvesting - , J. K. Malav; , Jagdish Rathod; , Surendra Kumar (Archives of Current Research International, 2025)
The present study aimed to determine the influence of Different Rates of Phosphorus and Zinc Application to Micronutrients uptake and DTPA Extractable Fe, Mn, Zn and Cu status after wheat (Triticum aestivum L.) harvesting. Organic source of plant nutrients helps in increasing soil organic matter and improving soil environments as well as meeting a part of the nutrients need of crops. Organic matter like FYM also helped in improving the micronutrient status of soil. Zn, Fe and Mn play very important role in photosynthesis and growth of plants. A field trial was conducted at Agronomy Instructional Farm, C. P. College of Agriculture, S. D. Agricultural University, Sardarkrushinagar, during Rabi season of 2020-21. The experiment encompassed of two aspects each having four levels of phosphorus (P0–0 kg P2O5 ha-1, P1–30 kg P2O5 ha-1, P2–60 kg P2O5 ha-1 and P3–90 kg P2O5 ha-1) and zinc (Zn0–0 kg Zn ha-1, Zn1–2.5 kg Zn ha-1, Zn2–5.0 kg Zn ha-1 and Zn3–7.5 kg Zn ha-1). A total of sixteen treatment combinations were laid out in randomized block design with factorial concept and replicated three times. Results revealed that different levels of phosphorus were found to be non-significant with respect to iron, manganese, zinc and copper content in grain and straw of wheat. But, significantly the highest Zn content in grain and straw was observed with the application of Zn @ 7.5 kg ha-1. Whereas, significantly the highest Fe, Mn, Zn and Cu uptake by grain and straw was observed with the application of 90 kg P2O5 ha-1 and Zn @ 7.5 kg ha-1; which remained at par with 60 kg P2O5 ha-1 and 5.0 kg Zn ha-1. Hence, significantly the highest DTPA-extractable Zn content in soil after harvest was recorded with the application of 7.5 kg Zn ha-1; which remained at par with 5.0 kg Zn ha-1. It is concluded that application of 90 kg P2O5 ha-1 and Zn @ 7.5 kg ha-1 significantly increased the iron, zinc, manganese and copper uptake as well as DTPA-extractable Zn status after harvest of wheat.